States at war. - Miller, Richard F., 1951- (States at War Ser., 2014)
While many Civil War reference books exist, there is no single compendium that contains important details about the combatant states (and territories) that Civil War researchers can readily access for their work. People looking for information about the organizations, activities, economies, demographics, and prominent personalities of Civil War states and state governments must assemble data from a variety of sources, with many key sources remaining unavailable online. This volume provides a crucial reference book for Civil War scholars and historians, professional or amateur, seeking i.